Infinitely many sign-changing solutions for an elliptic equation involving double critical Hardy–Sobolev–Maz’ya terms - Wang, Lixia; Zhao, Pingping; Zhang, Dong (Nonlinear Analysis: Modelling and Control, 2022)
In this paper, we consider the existence of infinitely many sign-changing solutions for an elliptic equation involving double critical Hardy–Sobolev–Maz’ya terms. By using a compactness result obtained in [C.H. Wang, J. Yang, Infinitely many solutions for an elliptic problem with double Hardy–Sobolev–Maz’ya terms, Discrete Contin. Dyn. Syst., 36(3):1603–1628, 2016], we prove the existence of these solutions by a combination of invariant sets method and Ljusternik–Schnirelman-type minimax method.